Effect of implementing childbirth preparation classes on women's self-efficacy and pregnancy outcomes - Awatiful Azza; Zusana A Sasarari; Nurafriani; Irmawati S; Muh Yunus (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Childbirth preparation classes play a crucial role in equipping pregnant women with the knowledge and skills necessary to face labor with confidence. Low maternal self-efficacy is often associated with increased anxiety, longer labor duration, and negative birth experiences. This study examines how implementing childbirth preparation classes affects women’s self-efficacy and pregnancy outcomes. Research Methodology: This quasi-experimental study used a pre-test and post-test control group design. 60 pregnant women in their third trimester were recruited and randomly assigned to either the intervention group (n=30), who received childbirth preparation classes, or the control group (n=30), who received standard antenatal care. The classes were conducted over four sessions, covering the labor process, pain management, relaxation techniques, and postpartum care. Self-efficacy was measured using the Childbirth Self-Efficacy Inventory (CBSEI), while pregnancy outcomes were assessed through medical records and post-delivery interviews. Result: The results showed a statistically significant increase in self-efficacy scores in the intervention group compared to the control group (p < 0.01). Additionally, women in the intervention group experienced shorter labor durations, lower cesarean section rates, and higher satisfaction with their birth experience. There were no significant differences in neonatal outcomes between the two groups. Conclusion: Implementing childbirth preparation classes positively influences maternal self-efficacy and improves several pregnancy outcomes. Integrating such programs into routine antenatal care can enhance maternal confidence and promote safer, more positive birth experiences